THE EFFECT OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS AN INTERVENING VARIABLE AT PT. SRIBOGA MARUGAME UDON SUPERMALL KARAWACI - Ulfa, Anita; Mikrad, Mikrad (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to determine and explain the effect of job satisfaction on organizational citizenship behavior at PT. Sriboga Marugame Udon Supermall Karawaci, to determine and explain the effect of organizational citizenship behavior (OCB) on employee performance, to determine and explain the effect of job satisfaction on employee performance, to determine and explain the effect of job satisfaction on employee performance with organizational citizenship behavior (OCB) as an intervening variable. This research is a quantitative study. The determination of the sample in this study used probability sampling techniques with simple random sampling techniques. The sample in this study was 50 employee respondents who worked at Supermall Karawaci. The data obtained were analyzed using the PLS (Partial Least Square) technique through Smart PLS software. The results of this study indicate that: 1) The results of the analysis show that Job Satisfaction has a significant effect on Employee Performance. 2) The results of the analysis show that Job Satisfaction has a significant effect on Organizational Citizenship Behavior. 3) The results of the analysis show that Organizational Citizenship Behavior has a significant effect on Employee Performance. 4) The results of the analysis show that Job Satisfaction has a significant effect on Organizational Citizenship Behavior through Employee Performance.